2000
DOI: 10.1021/ef990216q
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of a Synthetic Hindered-Phenol with Natural Fuel Antioxidants in the Autoxidation of Paraffins

Abstract: Changes in the liquid-phase oxidation of a cycloparaffinic/paraffinic solvent resulting from the introduction of natural and synthetic fuel antioxidants are studied by tracking the depletion of dissolved O 2 in a closed system at 185 °C and 3.2 MPa. A Jet-A fuel of reduced thermal stability is the source of natural fuel antioxidants that are introduced by making dilute (<20%) blends with the solvent. The synthetic hindered-phenol antioxidant BHT is added at concentrations of 3-50 mg/L. The individual and combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 11 publications
1
26
0
Order By: Relevance
“…Clay treatment removes polar surfactants from fuel, such as methyl phenols . Since methyl phenols are among the poorest antioxidants naturally present in fuel 18,19 and since deposit formation has previously been linked to the presence of natural antioxidants, which tend to be of relatively poor quality, it is likely that when methyl phenols are removed from the fuel via clay treatment, the fuel will become less effective at producing deposits. In other words, the fuel would be expected to produce a somewhat lower amount of deposition relative to polar content than other fuels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clay treatment removes polar surfactants from fuel, such as methyl phenols . Since methyl phenols are among the poorest antioxidants naturally present in fuel 18,19 and since deposit formation has previously been linked to the presence of natural antioxidants, which tend to be of relatively poor quality, it is likely that when methyl phenols are removed from the fuel via clay treatment, the fuel will become less effective at producing deposits. In other words, the fuel would be expected to produce a somewhat lower amount of deposition relative to polar content than other fuels.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of trace levels of naturally occurring heteroatomic species in jet fuel is known to be a primary contributor to thermal-oxidative instability, contributing to chemical reactions which ultimately produce undesirable bulk and surface insolubles. These heteroatomic species slow oxidation by interacting with peroxy radicals or hydroperoxides, and the reaction products ultimately lead to deposits. Most heteroatomic species present in jet fuel are more polar than the hydrocarbons which constitute the large majority of the fuel, and they are thus amenable to separation from the fuel by methods which adsorb or preferentially retain polars, such as normal-phase high-performance liquid chromatography (HPLC) or silica gel solid-phase extraction (SPE) procedures. , Although polar species in jet fuel have been analyzed by other methods, such as acidic or basic liquid−liquid extraction, no attempt has been made to analyze and quantify the primary jet fuel polar species responsible for deposit formation as a single class.…”
Section: Introductionmentioning
confidence: 99%
“…Among the modern inhibitors of free radical oxidation of organic and bioorganic substrates, antioxidants of the phenol type play the leading role: stabilizers of plastics, rubbers, and ca outchoucs; the most part of food antioxidants and drugs with antioxidant effect are also phenol compounds. [13][14][15][16][17][18][19][20][21][22][23][24] It seemed interesting to study the possibility of direct cross coupling of 1,4 diazinium systems with phenol derivatives aimed at developing new types of compounds with antiox idant activity.…”
Section: Methodsmentioning
confidence: 99%
“…The level of oxygenates in a fuel has been implicated as one of the factors in determining some of the stability properties of jet fuels. For example, it has been shown that the level of phenols present in a fuel is directly related to the buildup of deposits when the fuel is thermally stressed. These deposits may impact fuel circulation systems, such as filters and nozzles as well as other fuel system components, may impair proper performance of the aircraft systems, and could potentially lead to grounding of the aircraft. , It has been postulated that these polar species may play a role in the mechanisms of oxidative deposition. , Therefore, detection of oxygenate species in aviation fuels continues to be a major concern of the fuel industry.…”
Section: Introductionmentioning
confidence: 99%